2012
DOI: 10.1590/s1516-35982012000400021
|View full text |Cite
|
Sign up to set email alerts
|

Composição química e de ácidos graxos do músculo longissimus dorsi e da gordura subcutânea de tourinhos Red Norte e Nelore

Abstract: RESUMO -Objetivou-se com este trabalho avaliar a composição química e o perfil de ácidos graxos do músculo longissimus dorsi e da gordura subcutânea de tourinhos Red Norte e Nelore terminados em confinamento. Utilizaram-se 44 animais, sendo 22 Red Norte com peso vivo inicial médio de 367±30 kg e 22 do grupo Nelore com peso vivo inicial médio de 361±30 kg.Os animais receberam ração à vontade durante 112 dias e foram abatidos com 519 e 482 kg, respectivamente. Amostras do músculo longissimus dorsi e da gordura s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
1
10
0
3
Order By: Relevance
“…The present study also obtained results similar to those of Lopes et al (2012) and Pitombo et al (2013), the first working with feedlot Nellore bulls, obtained moisture, CP and ash values of 74.2%, 21.9% and 1.0%, respectively. In turn, Pitombo et al (2013) worked with Nellore X Guzerá bulls and reported values of moisture, EE and ash of 75.34%, 1.44% and 1.04%, respectively.…”
Section: Resultssupporting
confidence: 91%
“…The present study also obtained results similar to those of Lopes et al (2012) and Pitombo et al (2013), the first working with feedlot Nellore bulls, obtained moisture, CP and ash values of 74.2%, 21.9% and 1.0%, respectively. In turn, Pitombo et al (2013) worked with Nellore X Guzerá bulls and reported values of moisture, EE and ash of 75.34%, 1.44% and 1.04%, respectively.…”
Section: Resultssupporting
confidence: 91%
“…According to Daley, Abbott, Doyle, Nader, and Larson (2010), in a healthy diet, a satisfactory ratio should be approximately 1-to 4-fold more n-6 fatty acids than n-3 fatty acids. In the present study, the mean was 2.06 in the meat, which was an appropriate balance, because the excessive consumption of n-6 fatty acids can lead to the development of some degenerative diseases, such as cancer, diabetes, and arthritis (Lopes et al, 2012).…”
Section: Discussionmentioning
confidence: 56%
“…Oleic acid is usually the fatty acid found in largest quantity, and it features the ability to elevate blood high-density lipoprotein (HDL) levels (LOPES et al, 2012). On the other hand, among the classes of fatty acids present in the meat, only the sum of SFA was affected by the dietary regime.…”
Section: Resultsmentioning
confidence: 99%
“…oleic acid and CLA. The latter is found only in animal products, notably in ruminants (LOPES et al, 2012).…”
Section: Resultsmentioning
confidence: 99%